Obciążenia finansowe a sytuacja dochodowa rolnictwa indywidualnego w Polsce w latach 1985-1993 - Podstawka, Marian (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1995)
This is an assessment of the effect of financial burden of individual agriculture on its income before and after introducing the market economy to Poland. Under conditions of centrally planned economy (up to 1990) the total financial burden for individual agriculture on its net output was low, about 4.6-9.9%. But following the introduction of market economy, financial burden on net output and income for consumption and non-productive investments was 20% and 30%, respectively. The increase of financial burden in agricultural income is not due to changes in principles of their assessment but to unfavorable price relations for agriculture under market economy conditions, which contributes to a fall in actual income of individual farms. Actual agricultural income following the introduction of market economy in Poland dropped some 50% as compared to its level in the period of centrally controlled prices. Even more, down to 40% went that part of agricultural income which farmers use for investments.